2011
DOI: 10.1007/s12070-011-0280-0
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of FNAC and Histopathology of Thyroid Swellings

Abstract: Neck swelling is a common clinical presentation in ENT practice and it carries significant morbidity and even mortality if not managed properly. Thyroid swelling being the most common type we conducted a prospective study to assess the role of FNAC in diagnosing the nature of thyroid swelling and comparing its result with histopathology finding. It was observed that FNAC is a very reliable test having high sensitivity and specificity in thyroid swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 5 publications
9
22
2
Order By: Relevance
“…13,14 FNAC is a simple, safe, outpatient based and cost-effective modality of investigating thyroid disease with high sensitivity and specificity. 15 FNAC in the present study was found to have 80% sensitivity, 98.2% specificity and high diagnostic accuracy of 95.5% which is comparable with other studies. [16][17][18] The main indication for surgery in our series was the swelling itself either due to cosmetic reasons or fear of complications.…”
supporting
confidence: 90%
“…13,14 FNAC is a simple, safe, outpatient based and cost-effective modality of investigating thyroid disease with high sensitivity and specificity. 15 FNAC in the present study was found to have 80% sensitivity, 98.2% specificity and high diagnostic accuracy of 95.5% which is comparable with other studies. [16][17][18] The main indication for surgery in our series was the swelling itself either due to cosmetic reasons or fear of complications.…”
supporting
confidence: 90%
“…In a study, colloid goiter was the most common pathology observed (42.2%), and out of malignant cases, papillary carcinoma represented 71.4%, whereas follicular carcinoma represented 28.6%. 24 In our study, colloid goiter represented 64.5% of total lesions, whereas among malignant cases, follicular carcinoma was most common (52.6%), followed by papillary carcinoma (21.1%), Hurthle cell neoplasm (15.8%), and medullary carcinoma (10.5%). Cystic thyroid masses often set diagnostic pitfalls.…”
Section: Discussionmentioning
confidence: 48%
“…Rout et al (2011) [7] 96.05% Sinha and Ezzat (2012) [14] 93.6% Parikh et al (2012) [15] 90.24% Manshetty et al (2014) [8] 97.56% Present study 91.75%…”
Section: Causes Of Thyroids Swellingmentioning
confidence: 97%
“…of patients (70%) were seen in age group of 21-40 years which Section: Pathology was comparable with the results of mangshetty et al (2014) in age group of 21-40 (57.27%). [8] In the study of Rout et al (2011), [7] however noted, 30%patients were in age group of 21-30 years. Author and year of study Accuracy(% age)…”
Section: To Evaluate the Comparison Of Conventional Smearmentioning
confidence: 99%